ANALYSIS OF TRANSFORMER LOADING IMBALANCE AT THE FACULTY OF ENGINEERING, TANJUNGPURA UNIVERSITY - Siboro, Doni Aji Saputra; Arsyad, Muhammad Iqbal; Junaidi, Junaidi (Journal of Electrical Engineering, Energy, and Information Technology (J3EIT), 2024)
Electrical growth in UNTAN's Faculty of Engineering, especially the addition of buildings and facilities, increases the demand for electrical energy. Distribution transformers play a key role in lowering voltage to meet consumer needs. However, electrical load imbalances often occur due to the growth in demand and the use of electronic devices. The impacts include increased energy losses, threats to system reliability. neutral currents that can cause power losses. Therefore, further research is needed to analyze load imbalance and power loss in these transformers with reference to SPLN No.17 of 2014. In analyzing several calculations are used, namely Calculation of full load current, Calculation of distribution transformer loading, Calculation of load imbalance, Manual calculation of power loss, Calculation of energy loss, Analysis of load imbalance and balancing that can be done, Analysis of transformer loading. By analyzing the imbalance of transformer loading, based on calculations and simulations, transformer A is 18,6% with a power loss of 36,68 Watt, transformer B is 11,6% with a power loss of 107,91 Watt, transformer C is 13% with a power loss of 77,5 Watt, transformer D is 65,3% with a power loss of 386,99 Watt.